2019
DOI: 10.4067/s0717-95022019000301132
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and Differentiation of Mouse Spermatogonial Stem Cells on a Three-Dimensional Surface Composed of PCL/Gel Nanofibers

Abstract: Spermatogonial stem cells (SSCs) have self-renewal and differentiation capacity essential for sperm production throughout the male reproductive life. The electrospun polycaprolactone/gelatin (PCL/Gel) nanofibrous scaffold mimics important features of the extracellular matrix (ECM), which can provide a promising technique for the proliferation and differentiation of SSCs in vitro. The goal of the present study was to investigate the effects of PCL/Gel nanofibrous scaffold on the propagation and differentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
(46 reference statements)
1
7
0
Order By: Relevance
“…Liao et al have also used an irregular electrospun nanoparticle, in order to fabricate a network for SSCs culturing, and as a result, they have indicated that this structure resembled a basement membrane and also provided a suitable environment for the cell growth (Liao et al, 2006). Furthermore, Talebi et al have used a PCL–Gel scaffold to culture mouse spermatogonia and then have reported that the scaffold is able to maintain stem cell's viability and proliferation (Talebi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liao et al have also used an irregular electrospun nanoparticle, in order to fabricate a network for SSCs culturing, and as a result, they have indicated that this structure resembled a basement membrane and also provided a suitable environment for the cell growth (Liao et al, 2006). Furthermore, Talebi et al have used a PCL–Gel scaffold to culture mouse spermatogonia and then have reported that the scaffold is able to maintain stem cell's viability and proliferation (Talebi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, some studies showed that SCF/c‐kit system is very important for regulating survival, proliferation, apoptosis, differentiation and onset of meiosis in SSCs. As well, defects in SCF/c‐kit system of testis could lead to cessation of differentiation in these cells and to infertility (Lennartsson & Rönnstrand, 2012; Talebi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The use of synthetic polymers in tissue bioengineering is indicated because such polymers are biocompatible, have suitable physical-mechanical properties and elasticity to produce scaffolds. Among the synthetic materials used for the composition of scaffolds, there are the poly (L-lactic acid) (PLLA) ( 195 , 213 , 214 ), polypropylene, poly D, polycaprolactone (PCL) ( 215 ) and L-lactic-co-glycolic acid ( 208 ), which have already been used in the production of bone ( 227 ), cartilaginous ( 228 ), vascular ( 229 ) and dermal ( 230 ) scaffolds. Synthetic polymers can be combined with natural polymers, which improves their mechanical, physical and biocompatibility qualities.…”
Section: Discussionmentioning
confidence: 99%
“…Survival rate of SSCs cultured on PCL/Gelatin nanofibrous scaffolds was significantly higher than control group. Talebi et al [ 148 ] Neonatal mouse SSCs Electrospun nanofibrous PCL/Gel scaffold 4 weeks Number of colonies and viability rate of cultured cells on PCL/Gel scaffold increased. Expression of spermatogonial markers (Plzf and Inga6), meiotic and post meiotic genes (c-Kit, Tp1, and Prm1) significantly increased compared to the control group.…”
Section: Decellularized Extracellular Matrix Scaffoldsmentioning
confidence: 99%